Evaluation of moth bean genotypes for their resistance to yellow mosaic disease in northern Karnataka - Appu H. K.; Prema G. U. (Annals of Agricultural Research, 2024)
Moth bean (Vigna aconitifolia (Jaq.) Marechal) is characterized as one of the most drought hardy, short duration, annual legume crop. It is mainly grown in northern districts of Karnataka. Yellow mosaic, a viral disease transmitted by Bemisia tabaci causes detrimental effect on pulse crops by reducing their yield. Evaluation of moth bean germplasm lines against yellow mosaic disease under field conditions showed that out of 70 moth bean germplasm lines screened during 2019, one genotype (IC-36510) appeared moderately resistant, 15 genotypes showed susceptible reaction and remaining 54 genotypes showed highly susceptible reaction. Among 168 moth bean genotypes screened during 2020, none of the genotypes showed highly resistant and moderately resistant reaction. Eight genotypes showed susceptible reaction and remaining 160 genotypes were found to be highly susceptible.